Alternatif Perancangan Struktur Atas Gedung Kuliah IAIN Kota Palu Sulawesi Tengah - Wicaksono, Muh. Ramdhan Ainun; Setiawan, Arman; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2024)
The use of steel structure material as a building structure has not been as widespread as in other countries, generally steel material is used to build bridges. But if you use the strength of the steel structure as a working load bearer, it will result in a stronger profile design, and easy to implement. In this research uses a steel structure as the construction of the IAIN Palu Lecture Building has a fourfloors with a building length of 83.25 m, a building width of 70 m and a building height of 16.8 m. This research re-plans with a steel frame in its structure. This building planning refers to SNI 1726:2019, SNI 1727:2020, and SNI 1729-2020. Software used ETABS v.19 and Autocad 2019. Load analysis in the form of dead load, live load, and earthquake. The primary beam B1 WF 800.300.14.26; B2 WF 582.300.12.17; B3 WF 390.300.10.16 and L1 WF 340.250.9.14; column K1 WF 900.300.16.28; K2 WF 350.350.12.19.; and K3 WF 700.300.13.24.